Clinicopathological and genetic study of a rare occurrence: Malignant transformation of fibrous dysplasia of the jaws. Issue 1 (5th January 2022) - Shi, Ruirui; Li, Xuefen; Zhang, Jianyun; Chen, Feng; Ma, Ming; Feng, Yanrui; Li, Tiejun
Abstract: Background: Malignant transformation of fibrous dysplasia (FD) is very rare and little is known about this occurrence. Methods: We present the detailed clinical course of three cases of osteosarcoma arising from FD of the jaws and explore the genetic aberrations by Sanger sequencing, whole‐exome sequencing (WES) and immunohistochemistry (IHC). A literature review of important topics related to this occurrence was also performed. Results: It was observed that patients with secondary sarcoma from FD showed a wide range of ages, with most during the third decade. Female and males were equally affected. Craniofacial bones and femurs were the most affected sites. High‐risk factors for this occurrence included polyostotic FD, McCune‐Albright syndrome and excess growth hormone. Notably, a potential relationship between thyroid hormones and sarcoma development was suggested in one patient, who began to show malignant features after hypothyroidism correction. Sanger sequencing revealed GNAS mutations of FD retained in all malignant tissues. Additionally, abnormal TP53 was demonstrated in all three cases by WES and IHC. WES also revealed two other driver mutations, ROS1 and CHD8, and large amounts of somatic copy number alterations (CNAs) where various oncogenes and tumour suppressors are located. Conclusion: This study demonstrated and reviewed the clinical features and risk factors for a rare occurrence, secondary sarcoma from FD, and provided important new knowledge about its genetics. Abstract : Whole exome sequencing revealed the underlying genetic mechanisms of osteosarcoma arising from fibrous dysplasia of the jaws. Significant somatic single nucleotide variations, including TP53, ROS1 AND CHD8, as well as large amounts of somatic copy number alterations were demonstrated.